Literasi keuangan dan kesejahteraan rumah tangga petani di Gorontalo: Financial literacy and welfare of farmer households in Gorontalo - Adam, Echan; Halid, Amir (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: The decline in the Farmer's Exchange Rate index of Gorontalo Province in 2020 (96.93) compared to before four years ago (>100) indicates a decline in farmer welfare. On the other hand, increasing financial literacy is the government's focus on realizing people's welfare. The purpose of this study was to analyze the level of financial literacy of farmer households, as well as its effect on the farmer household welfare in Gorontalo Province. Methods: The sample was selected based on the purposive sampling technique with a total of 120 farmer households. The data analysis technique uses a linear regression model with a dummy variable technique and adds variable social support of the farmer's household in estimating the effect of financial literacy on the farmer's household welfare. Results: The results of this study indicate that financial literacy which consists of variable knowledge of financial institutions and ownership of savings account, has a positive and significant effect on the farmer's household welfare. Farmers who have literacy and access to capital at financial institutions are predicted to be 46.57% more likely to prosper than those who do not. Likewise, farmers who have savings accounts at financial institutions are estimated to be 44.1% more likely to prosper than farmers who do not have savings accounts. The variable of social support of farmer households, such as household heads’ age, number of household members, and number of employed households, also affected the farmer household's welfare in Gorontalo Province. Conclusion: Financial literacy determines the level of welfare of farmer households in Gorontalo Province. Efforts to increase the level of financial literacy of farmers in Gorontalo Province need to be realized in the form of financial education programs in order to support Government programs.